Sengketa Pajak atas Koreksi Biaya Royalti dan Secondary Adjustment (Studi Kasus Putusan Banding PT XYZ) - Widhi Nugroho Budi Prasetyo; Dahlia Sari (Politeknik Ganesha Medan, 2023)
The purpose of this study is to analyze transfer pricing disputes over royalty cost correction and the imposition of Secondary Adjustment and provide recommendations both to the tax authorities in the audit process and to taxpayers in the company's financial reporting in the future. Based on the object of research, there are differences in the results of the decision on the dispute over the correction of royalty costs of PT XYZ for the 2009 to 2015 tax years and there has been no research on the imposition of Secondary Adjustment in previous studies. The research method used is a qualitative method with a case study approach by looking at secondary data in the form of PT XYZ Appeal Decisions for tax years 2009, 2011, 2013, 2014 and 2015 as well as interviews with consultants, tax auditors and objection reviewers. The results of the study concluded that the royalty fees charged were not in accordance with the arm’s length principles. The tax auditors is less than optimal in conducting the examination by not imposing Secondary Adjustment for the examination of Tax Years 2013, 2014 and 2015.